Cam Impingement of the Knee: Arthroscopic Correction of Posteromedial Tibiofemoral Incongruence - Konrad Malinowski, M.D., Ph.D.; Magdalena Koźlak, P.T., M.Sc.; Marcin Mostowy, M.S.; Robert F. LaPrade, M.D., Ph.D.; Michał Ebisz, M.D.; Przemysław A. Pękala, M.D., Ph.D. (Arthroscopy Techniques, 2022)
One of the anatomic variations observable within the knee joint is a reduction in the posterior curvature of the femoral metaphysis proximal to the medial femoral condyle. This curvature is usually concave enough to fit the posterior horn of the medial meniscus (PHMM) during full knee flexion. A reduction in curvature may result in posteromedial tibiofemoral incongruence, a condition characterized by compression of the PHMM in full knee flexion, similar to cam incongruence in the hip joint. Clinical symptoms may occur in deep knee flexion, and progressive degeneration of the PHMM can be observed if this position is not prohibited. For patients in whom activity modification and conservative treatment have failed, surgery may be indicated. We describe arthroscopic treatment allowing for final intraoperative confirmation of the clinical indication for posteromedial tibiofemoral incongruence correction, as well as allowing for the least possible, yet sufficient, amount of correction.